Development of mobility behaviour in tourism. Evaluation of requirements in mobility behaviour of tourists in rural and inner-city regions. - Weber, Marcel (Trialog Publishers, 2020)
The continuous growth of tourism is one of the main causes of an increase in traffic volume in rural and inner-city regions. Taking into account the Paris Agreement on climate protection, pushing forward with sustainable mobility concepts is an obligatory task in the tourist industry. In order to be able to develop future-oriented measures with regard to the accessibility of destinations, a primary goal was an in-depth evaluation of tourist mobility behaviour requirements and the development of a requirements catalogue based on this evaluation.
Keywords: Verkehr; Reiseverkehr; Tourismus; Verkehrsverhalten; Evaluation; Städtetourismus; Ländlicher Raum; Verkehrsaufkommen; Verkehrskonzept; Nachhaltigkeit; Multimodalität; Buchung